Previdência social: análise dos fatores que afetam a necessidade de financiamento do regime geral - Dantas, Emanuel de Araújo (2009)
This dissertation makes an analysis of the main factors that have affected the result of the General Regime of Social Security – RGPS, pointing the reasons that generate the deficit and its relation with the market of formal work. Search to identify a set of factors that exerts influence in the prescription components and expenditure with benefits of the RGPS. Of this form, two models, one for esteem of the equation revenues of the RGPS and another one for the equation of the expenditures with benefits of the RGPS are used. An identity for verification of the result (balance) of the accounts of the RGPS. The aforementioned models were submitted to the multiple regression analysis’s method applied to the econometer series to the referencial light. The results confirm the influence of the formal labor factors, demographics, minimum salary and industrial production in the balances, benefits and financial balances of the GRSS. On the basis of these premises, utilizes the parameters of the equations to be able to estimate the future results from 2008 through 2050.